2009
DOI: 10.1002/art.24221
|View full text |Cite
|
Sign up to set email alerts
|

Molecular framework for response to imatinib mesylate in systemic sclerosis

Abstract: Systemic sclerosis (SSc) is an autoimmune disease in which the tyrosine kinases platelet-derived growth factor receptor (PDGFR) and Abl are hypothesized to contribute to the fibrosis and vasculopathy of the skin and internal organs. Herein we describe 2 patients with early diffuse cutaneous SSc (dcSSc) who experienced reductions in cutaneous sclerosis in response to therapy with the tyrosine kinase inhibitor imatinib mesylate. Immunohistochemical analyses of skin biopsy specimens demonstrated reductions of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 72 publications
1
77
0
Order By: Relevance
“…5,6,[8][9][10] Despite the fact that imatinib's antifibrotic mechanism is not completely known, Akhmetshina et al 4 concluded that imatinib might induce regression of fibrosis via its inhibitory effects on collagen synthesis, leading to a relative increase in matrix degradation, rather than by exerting direct effects on matrix degradation. Mild to moderate severity of superficial edema, most commonly on the eyelids, is reported in 48-65% of patients treated with imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,[8][9][10] Despite the fact that imatinib's antifibrotic mechanism is not completely known, Akhmetshina et al 4 concluded that imatinib might induce regression of fibrosis via its inhibitory effects on collagen synthesis, leading to a relative increase in matrix degradation, rather than by exerting direct effects on matrix degradation. Mild to moderate severity of superficial edema, most commonly on the eyelids, is reported in 48-65% of patients treated with imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence supports the use of skin, lung, and peripheral blood transcriptomes as SSc biomarkers to quantify interpatient heterogeneity, to identify dysregulated molecular pathways underlying disease, and to identify appropriate patients for specific SSc therapies (6)(7)(8)(9). These studies have identified remarkable homogeneity in skin biopsies obtained from the same patient such that transcriptomic profiles of clinically unaffected back and clinically affected forearm biopsies are nearly identical (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Microarray studies have also been employed to identify specific patterns of gene expression in SSc-associated pulmonary fibrosis [119] and pulmonary hypertension [120], and have identified a subset of SSc patients who display a TGF-b signature in their skin [121]. Thus, global gene-expression studies promise to provide mole cular signatures that will be useful as molecular biomarkers for the diagnosis of SSc, identification of its clinical subsets, evaluation of effectiveness of disease-modifying therapies, and stratification of patients who may respond and benefit from specific therapies, as recently shown for imatinib mesylate [121,122].…”
Section: Analysis Of Gene Expression Employing Microarraysmentioning
confidence: 96%